Investigating the relationship between success factors and student participation in online and blended learning in adult education. (27th February 2019) - Blieck, Yves; Kauwenberghs, Kurt; Zhu, Chang; Struyven, Katrien; Pynoo, Bram; DePryck, Koen
Abstract: Online and blended learning (OBL) is valued, but it also offers challenges. Literature indicates that OBL can enhance access to education and increase flexibility for students. However, the reported dropout rates indicate that student participation in OBL programmes is a concern. Scientifically valid knowledge about how factors that help students participate in OBL are related to student participation is necessary for quality improvement of OBL. This knowledge can help professionals determine what they need to improve in their institution and how to prioritize those improvements. In this study, we report on the validation of a quality instrument with indicators related to quality dimensions present in quality management frameworks and important success factors that aid student participation in OBL. These success factors are as follows: credibility, transparency, flexibility, accessibility, interactivity, personalization, and productivity. The partial least squares structural equation modelling (PLS‐SEM) method is suitable for validating complex models in studies where predictive accuracy is important. According to adult students, all success factors, except flexibility, are important for aiding OBL participation. Adult students perceive that the quality dimensions of learning activities and student support (related to interactivity) deserve priority in improving participation in OBL in adult education. Lay Description: What is currently known about the subject matter? Dropout rates indicate that student participation is a concern in online and blended learning. Existing institutional quality management frameworks report similar quality dimensions. Scholars investigated these dimensions and how they are related and student satisfaction. These studies do not address the question of how institutions can improve participation. What does this paper add to this? We validate a quality instrument with indicators related to factors that aid participation and quality dimensions. Knowledge about how these factors are related to participation is relevant for quality improvement. We assess the relations between the factors and the predictors for participation. The links of the indicators with quality dimensions informs quality improvement. What are the implications for practitioners? The quality instrument is sufficiently valid and reliable to use as a survey to assess quality. According to adult students most factors, except flexibility, are important for participation. The factor "interactivity" is the main predictor for participation. Improving the quality dimensions "design of learning activities" and "student support" need priority.